Kontribusi motivasi belajar, USBN, dan jarak rumah terhadap prestasi belajar siswa - Woro Hartini; Supriyoko Supriyoko; Samsi Haryanto (Teacher in Educational Research, 2021)
Penelitian ini bertujuan untuk mengetahui: (1) Untuk mengetahui kontribusi motivasi belajar siswa, USBN, dan jarak rumah ke sekolah terhadap prestasi belajar siswa SMP; (2) Untuk mengetahui kontribusi motivasi belajar siswa terhadap prestasi belajar siswa; (3) Untuk mengetahui adakah kontribusi nilai USBN terhadap prestasi belajar siswa SMP; dan (4) Untuk mengetahui adakah kontribusi jarak rumah ke sekolah siswa terhadap prestasi belajar siswa. Penelitian ini dilaksanakan di kelas VII SMP sebagai populasinya 187 siswa. Analisis data menggunakan program SPSS versi 16. Hasil penelitian ini menunjukkan bahwa (1) Terdapat kontribusi motivasi belajar, USBN dan jarak rumah ke sekolah terhadap prestasi belajar siswa; (2) Terdapat kontribusi motivasi belajar terhadap prestasi siswa dengan sumbangan efektif sebesar lima puluh satu kom sembilan persen; (3) Ada kontribusi USBN terhadap prestasi siswa dengan sumbangan efektif sebesar delapan koma satu persen; dan (4) Tidak Terdapat kontribusi jarak rumah ke sekolah terhadap prestasi siswa. The contribution of learning motivation, USBN and home distance toward the learning achievement of students  Abstract: This research is aimed: (1). To find out how big the student learning achievement, USBN and the home distance toward the student learning achievement of SMP Negeri 1 Ngaglik; (2). To find out is there an influence of the student learning motivation on the learning achievement of students SMPN 1 Ngaglik; (3). To find out is there an influence of USBN value on the student learning achievement of SMP Negeri 1 Ngaglik; (4). To find out is there an influence of home distance on the student learning achievement of SMP Negeri 1 Ngaglik.  This research is done in Grade VII SMP Negeri 1 Ngaglik a population of 187 students. The questionnaire analysis is using the program SPSS version 16 While the hypothesis test uses the analysis of double regression by 3 predictors. The research result shows that (1). There is a contribution of learning motivation, USBN and home distance toward the student learning achievement and contribution R square for 60,01 % (category gives the big contribution), is explained by other variables that do belong to this research; (2) There is the contribution of learning motivation toward the student achievement with, and effective contribution for 51,91 %; (3). There is the contribution of USBN toward the student achievement with smaller than 0,05 and an effective contribution of 8,10%. And 4). There is no contribution of the home distance toward student achievement.